Pelaksanaan Keselamatan dan Kesehatan Kerja (K3) Di Perusahaan Dalam Wilayah Kota Yogyakarta.. Application of Occupational Safety and Health (K3) at Companies in Yogyakarta City. - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACT The application of occupational safety and health in a company is an attempt to prevent accident at workplace and illness due to the work. The objective of research is to reveal factors that hinder the application of occupational safety and health. This research is a normative legal research. Out of 49 companies having cases of accident at workplace in Yogyakarta in 2001, six companies were selected randomly as sample. Out of 1327 workers, 135 workers were picked up in a random manner as sample. The instrument of collecting data were documentaries study, questionnaire and interviews. The variables consisted of dependent variable, namely the applications of occupational safety and health and independent variable namely factors that hindered the applications of occupational safety and health. The collected data were classified, selected and further analysed using qualitative method to answer the problem. The result of research reveals that the application of occupational safety and health was not properly performed. Means and infrastructure for labour inspection had not adequately provided. The inspections of labour had not been perfectly performed. The law enforcement by judicial institutions was never carried out. Employers considered occupational safety and health were an additional expensive burden. Employers was not special division in the company that was responsible for occupational safety and health. It was delegated to the Staff Division. Employers had not yet educated and trained the workers on the occupational safety and health. The employers did not have yet own human resources who knew well about occupational safety and health. The employers had not yet applied Management System for Occupational Safety and Health (SMK3) in the workplace. Policy and program of occupational safety and health had not been stipulated and written form. The establishment of Committee for Advancement of Occupational Safety and Health (P21(3) appeared to merely full fill the regulations. The members of Committee for Advancement of Occupational Safety and Health consisted only of workers at the company.